The impact of Trichoderma spp. treatment on physical and biochemical properties of oil palm (Elaeis guineensis Jacq.), and associated soil fungal biodiversity under challenge with Ganoderma boninense - Khoo, Chee Chang (2025)
Oil palm (Elaeis guineensis Jacq.) is a crucial crop in Malaysia, significantly contributing to the economy and global food supply. However, it is threatened by basal stem rot (BSR) disease caused by Ganoderma boninense without early infection symptoms, leading to reduced yields and premature palm death. This study aimed to evaluate the efficacy of Trichoderma spp. formulations in supporting plant growth and suppressing BSR disease under semi-controlled conditions. Additionally, it explored fungal biodiversity in the oil palm rhizospheric soil and identified potential early detection approaches for BSR through changes in fungal community composition.